The Btk tyrosine kinase is a major target of the Bcr-Abl inhibitor dasatinib - Hantschel, Oliver (National Academy of Sciences, 2007)
Dasatinib is a small-molecule kinase inhibitor used for the treatment of imatinib-resistant chronic myelogenous leukemia (CML). We have analyzed the kinases targeted by dasatinib by using an unbiased chemical proteomics approach to detect binding proteins directly from lysates of CML cells. Besides Abl and Src kinases, we have identified the Tec kinases Btk and Tec, but not Itk, as major binders of dasatinib. The kinase activity of Btk and Tec, but not of Itk, was inhibited by nanomolar concentrations of dasatinib in vitro and in cultured cells. We identified the gatekeeper residue as the critical determinant of dasatinib susceptibility. Mutation of Thr-474 in Btk to Ile and Thr-442 in Tec to Ile conferred resistance to dasatinib, whereas mutation of the corresponding residue in Itk (Phe-435) to Thr sensitized the otherwise insensitive Itk to dasatinib. The configuration of this residue may be a predictor for dasatinib sensitivity across the kinome. Analysis of mast cells derived from Btk-deficient mice suggested that inhibition of Btk by dasatinib may be responsible for the observed reduction in histamine release upon dasatinib treatment. Furthermore, dasatinib inhibited histamine release in primary human basophils and secretion of proinflammatory cytokines in immune cells. The observed inhibition of Tec kinases by dasatinib predicts immunosuppressive (side) effects of this drug and may offer therapeutic opportunities for inflammatory and immunological disorders.